Outcome of 12‐month surveillance colonoscopy in high‐risk patients in the National Health Service Bowel Cancer Screening Programme. (29th August 2013) - Lee, T. J. W.; Nickerson, C.; Goddard, A. F.; Rees, C. J.; McNally, R. J. Q.; Rutter, M. D.
Abstract Aim Current British guidelines recommend surveillance colonoscopy at 12 months for individuals found to have five or more adenomas, or three or more adenomas of which at least one is ≥ 1 cm in size. This study describes the yield of surveillance colonoscopy in this group and explores patient and clinical factors that may be associated with the presence of advanced adenomas or cancer at surveillance. Method Data were retrieved from the national database of the National Health Service Bowel Cancer Screening Programme. The detection of advanced colonic neoplasia (ACN, cancer or advanced adenoma) was used as the main outcome variable. Multivariable analysis was used to analyse relationships between patient factors (age, gender, body mass index, smoking and alcohol use) and clinical findings (number, size and nature of adenomas detected during index colonoscopy) with the outcome variable. Results One‐thousand, seven‐hundred and sixty individuals were included in the study. The yield of ACN at 12‐month surveillance was 6.6% (116/1760), of which 14/1760 (0.8%) had colorectal cancer. Nine (64.3%) of these 14 cancers were Dukes A at diagnosis. The presence of a villous adenoma or a right‐sided adenoma at screening colonoscopy was associated with ORs of 1.98 (95% CI: 1.11–3.53, P = 0.012) and 1.76 (95% CI: 1.13–2.74, P = 0.020), respectively, for detection of ACN at surveillance. Conclusion Twelve‐month surveillance colonoscopy is necessary in this group of patients. The presence of villous or proximal lesions at baseline is associated with increased risk of ACN at surveillance. Site and histological type of baseline lesions may be relevant for determining the surveillance interval.